1996
DOI: 10.1007/bf00596587
|View full text |Cite
|
Sign up to set email alerts
|

Medulloblastoma in children: CT and MRI findings

Abstract: Our purpose was to determine whether medulloblastoma (MB) shows specific neuroradiological features which may be employed in differential diagnosis from other common posterior cranial fossa tumours in childhood. Preoperative MRI was performed on 20 children with MB, and preoperative CT in 17 of them. All underwent surgery and histopathological diagnosis. There was a constant relationship between high density on CT and low signal on T1-weighted images. Signal behaviour on T2-weighted images and the degree of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 10 publications
4
47
0
7
Order By: Relevance
“…Arakawa et al[ 4] reported that 7.5% of medulloblastomas appeared as nonenhanced masses. The presence of enhancement has no correlation with the pathological subtype [8], and nonenhancement is not a specific feature of congenital medulloblastoma [7]. However, as nonenhancement is extremely rare in congenital medulloblastoma, the radiological features of the present case were such that it was difficult to make the correct preoperative diagnosis.…”
Section: Discussionmentioning
confidence: 43%
“…Arakawa et al[ 4] reported that 7.5% of medulloblastomas appeared as nonenhanced masses. The presence of enhancement has no correlation with the pathological subtype [8], and nonenhancement is not a specific feature of congenital medulloblastoma [7]. However, as nonenhancement is extremely rare in congenital medulloblastoma, the radiological features of the present case were such that it was difficult to make the correct preoperative diagnosis.…”
Section: Discussionmentioning
confidence: 43%
“…Survival rates of patients affected with these lesions have improved significantly over the past 30 years, with recent treatment strategies in standard-risk patients producing 5-year survival rates surpassing 80% [16] and more aggressive protocols in patients with high-risk disease resulting in 5-year survival rates ranging from 60 to 70% [17]. In contrast to PAs, pediatric medulloblastomas are often midline with demonstrated involvement of the vermis and/or fourth ventricle and variable extension into the hemispheres [19]. Due to elevated tumor cellularity and an increased proportion of nuclear area, medulloblastomas demonstrate more restricted diffusion of water than ependymomas and astrocytomas, and are hyperintense on DWI relative to these other histologies.…”
Section: Discussionmentioning
confidence: 99%
“…By bringing four studies with large cohorts together into one global data set, we aimed at generating a representative number of pediatric medulloblastomas [5,[7][8][9]. We chose 4 large studies based on a PubMed search (keywords medulloblastoma and MRI) reporting a total of 118 patients.…”
Section: Pediatric Cohortmentioning
confidence: 99%
“…We therefore merged four large cohorts [5,[7][8][9] into one global data set ( Table 4). The patient cohorts resembled the accepted, classical phenotype of childhood medulloblastoma [12].…”
Section: Pediatric Medulloblastomamentioning
confidence: 99%
See 1 more Smart Citation